(untitled) (Research, Society and Development, 2023)
Objective: to analyze the progress in the elimination of leprosy as a public health problem through disease monitoring indicators. Methodology: This is a cross-sectional, retrospective, descriptive and documentary-based research based on confirmed and notified leprosy cases in the Notifiable Diseases Information System from 2001 to 2016 in Brazil. After data collection, an analysis of disease monitoring indicators was carried out with discussion based on current literature. Results: Endemic parameters showed a tendency to decrease in all regions, except for the proportion of degree 2 of physical disability among new cases, which has been increasing and is higher in the South and Southeast; decrease in the proportion according to gender, revealing a higher prevalence in males; and an increase in the proportion according to operational classification, indicating an increase in the percentage of multibacillary cases among new cases. In addition, no region reached a hyperendemic value, however, only the South recorded low endemicity for two of the parameters used. It can be observed, therefore, that the reduction of the endemic was not uniform, neither by indicator used nor by region, and even with predominantly a tendency to reduce the endemic, it is not possible to predict when it will be considered eliminated. It is concluded that efforts to combat the disease should continue and further studies should be encouraged to assess the effectiveness and specificity of each indicator in the elimination of leprosy.